PENATALAKSANAAN PADA WANITA USIA 47 TAHUN DENGAN HIPERKOLESTROLEMIA MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Retno Arienta Sari (Journal of Health Science and Physiotherapy, 2022)
Background: The prevalence of hypercholesterolemia in Indonesia in the 55-64 year age group increases with age up to 15.5%. Hypercholesterolemia can also cause cardiovascular and metabolic diseases. The incidence of hypercholesterolemia is associated with risk factors due to unhealthy lifestyle. Objective: Application of evidence-based medicine for family doctors by identifying risk factors, clinical problems, and patient management based on the framework for solving patient problems with a patient centered and family approach. Method: This study is a case report. Primary data were obtained through history taking, physical examination, supporting examination and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Results: The patient complained of soreness in the neck since 2 months ago and gotten worse in the last 1 weeks so that it interferes with patients to carry out daily activities. Clinically the patient was diagnosed with hypercholesterolemia (ICD 10:E78.00). In the knowledge assessment, the score before the intervention was 6 (low) and after the intervention it was 9 (high). In the aspect of diet there is a change in the number of calories and the type of food that is appropriate. In the aspect of physical activity there is a change in physical activity at least 3 times a week. Conclusion: After the holistic and comprehensive management, patient and families gained an increase in knowledge about the disease that suffered by patients by 30 points and changes in diet and physical activity